The Paradox of Inwardness in Kant and Kierkegaard: Ronald Green's Legacy in Philosophy of Religion. Issue 4 (December 2016) - Palmquist, Stephen R.
Abstract: Aside from bioethics, the main theme of Ronald Green's lifework has been an exploration of the relation between religion and morality, with special emphasis on the philosophies of Immanuel Kant and Søren Kierkegaard. This essay summarizes and assesses his work on this theme by examining, in turn, four of his relevant books. Religious Reason (1978) introduced a new method of comparative religion based on Kant's model of a rational religion. Religion and Moral Reason (1988) expanded on this project, clarifying that religious traditions cannot be reduced to their moral grounding. Kierkegaard and Kant: The Hidden Debt (1992) offered bold new evidence that Kant, not Hegel, was the philosopher whose ideas primarily shaped Kierkegaard's overtly religious philosophy; both philosophers focused on the problem of how to understand the relation between moral reasoning and historical religion. And Kant and Kierkegaard on Time and Eternity (2011) republished ten essays that explore various aspects of this theme in greater depth. I argue that throughout these works Green defends a "paradox of inwardness": principles or ideals that are by their nature essentially inward end up requiring outward manifestation in order to be confirmed or fully justified as real.